Drug Induced Toxic Epidermal Necrolysis - A Retrospective Study In South India - Karthikeyan K; Hemanth Kumar R; Thappa Devinder Mohan; D′Souza Mariette; Singh Sirisha (Wolters Kluwer Medknow Publications, 1999)
Toxic epidermal necrolysis (TEN) is a severe mucocutaneous reaction pattern characterized by fever, systemic toxicity, tenderness, erythema and wide-spread exfoliation. A retrospective analysis from January 1990 to December 1996 was undertaken to see the changing trends and outcome of this disorder in a third world country. A total of eleven cases were found. Their mean age was 33.09 years and male to female ratio was 2.6:1. Various drugs implicated were paracetamol (2 cases), co-trimoxazole (2 cases), aspirin (1 case), thiacetazone (1 case), streptomycin (1 case), etc. On an average, the patients developed TEN at the interval of 4.68 days following the drug intake. Fever was presenting symptom in all cases and burning sensation preceded it in 6 of them. Percentage area. Involved ranged from 40% to 90%. Other target areas involved in order of decreasing frequency were oral mucosa (9 cases) genitalia (8 cases), eye (5 cases), palms and soles (3 cases). Oral prednisolonoe therapy was started in all cases in the range of 20 to 80 mg. According to the severity, extent of lesion and body weight. Epithelisation of denuded areas took an average of 10.6 days. Complications in the form of secondary infection (3 cases), septicaemia and death (1 case) and symblepheron formation (1 case) were noted.